A Novel Approach for a Chip-Sized Scanning Optical Microscope - Joan Canals; Nil Franch; Victor Moro; Sergio Moreno; Juan Daniel Prades; Albert Romano-Rodríguez; Steffen Bornemann; Daria D. Bezshlyakh; Andreas Waag; Florian Vogelbacher; Stefan Schrittwieser; Katarzyna Kluczyk-Korch; et al. (Micromachines, 2021)
The recent advances in chip-size microscopy based on optical scanning with spatially resolved nano-illumination light sources are presented. This new straightforward technique takes advantage of the currently achieved miniaturization of LEDs in fully addressable arrays. These nano-LEDs are used to scan the sample with a resolution comparable to the LED sizes, giving rise to chip-sized scanning optical microscopes without mechanical parts or optical accessories. The operation principle and the potential of this new kind of microscope are analyzed through three different implementations of decreasing LED dimensions from 20 µm down to 200 nm.